Excavation Method of Reducing Blasting Vibration in Complicated Geological Conditions - Lixiang Xie; Wenbo Lu; Jincai Gu; Gaohui Wang (Shock and Vibration)
Drilling and blasting method as a common excavation method is widely used in the underground engineering construction. However, in the complicated geological conditions, the path of blasting excavation available has limitation, and then the larger blasting vibration is produced, which influence the stability and safety of the protected structure. To effectively reduce the blasting vibration by optimizing the blasting excavation method, firstly, the site test on blasting vibration is conducted to obtain the blasting vibration data; secondly, the LS-DYNA software is applied to simulate the vibration generated by blasting in site test, based on back analysis on the blasting vibration, the mechanical parameters of the rock mass are obtained, and they are used to simulate six different types of blasting excavation method. According to the analysis on them, the reasonable blasting excavation method is proposed to reduce the blasting vibration which can satisfy the blasting safety regulation.